Sosialisasi dan Pengenalan Augmented Reality sebagai Inovasi Pembelajaran Praktik dalam Kurikulum SMK - Supardi, Rafsanjani; Amiruddin, Amiruddin; Setialaksana, Wirawan; Rasyid, Ramli; SN, Ulfaizah (Jurusan Matematika FMIPA UNM, 2025)
This program aims to introduce Augmented Reality (AR) technology as an interactive learning medium for practical instruction in Vocational High Schools (SMK). Within the context of educational digitalization and the challenges posed by the Fourth Industrial Revolution, the implementation of AR technology presents an alternative solution to enhance students’ interest, motivation, and learning outcomes. The outreach activities targeted both teachers and students through interactive lectures and demonstrations of mobile-based AR applications. The outcomes indicate improved teacher understanding of AR’s potential to support practice-oriented curricula, along with a growing readiness to integrate AR into the teaching and learning process. This initiative is expected to serve as a foundational step toward a more adaptive and technology-driven educational transformation.